Predator performance of Coccinella transversalis and its molecular identification (Bangladesh Journal of Zoology, 2019)
Predatory efficacy of Coccinella transversalis (Coleoptera: Coccinellidae) on three detrimental agriculturally important aphids (Aphis craccivora, A. fabae and A. gossypii) was studied under laboratory condition. The 4th instar larvae of C. transversalis consumed highest (21.56 ± 1.72) number of A. craccivora aphids followed by A. fabae (12.33 ± 1.74) and A. gossypii (13.99 ± 0.77). Life cycle studies of C. transversalis on the above three aphid species revealed that it took maximum (27.66 ± 3.06) days to complete life cycle while reared on A. craccivora followed by A. fabae (25.66 ± 0.58 days) and A. gossypii (22.33 ± 1.52 days) respectively. As C. transversalis is a potential predator, an attempt was taken to identify this biological control agent based on mitochondrial cytochrome c oxidase (COI) gene sequence. Sequenced gene was submitted to the NCBI GenBank database (Accession NO. MG 587947.1) followed by proper procedure. Phylogenetic relationship of the beetle was constructed based on mitochondrial COI gene. The nucleotide composition analysis revealed that the value of A+T (69.3%) was greater than G+C (30.7%). Such study of C. transversalis would be helpful in biological control programme of aphid pest.Bangladesh J. Zool. 47(2): 229-241, 2019